2008
DOI: 10.1143/jpsj.77.034607
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ballistic Thermal Conduction in the One-DimensionalS=1/2 Heisenberg Antiferromagnetic Spin System Sr2CuO3

Abstract: We have measured the thermal conductivity of the one-dimensional (1D) S = 1/2 Heisenberg antiferromagnetic spin system of Sr

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 34 publications
7
80
2
Order By: Relevance
“…spinon-defect Thus we have l −1 mag = l −1 0 + l −1 sp , where l 0 describes the T -independent spinon-defect scattering whereas l sp (T ) accounts for the T -dependent spinon-phonon scattering. For the latter, we assume a general umklapp process with a characteristic energy scale k B T * u of the order of the relevant phonon energies, which is commonly used in literature [1,2,4,6,35]. Thus we get the expression,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…spinon-defect Thus we have l −1 mag = l −1 0 + l −1 sp , where l 0 describes the T -independent spinon-defect scattering whereas l sp (T ) accounts for the T -dependent spinon-phonon scattering. For the latter, we assume a general umklapp process with a characteristic energy scale k B T * u of the order of the relevant phonon energies, which is commonly used in literature [1,2,4,6,35]. Thus we get the expression,…”
Section: Resultsmentioning
confidence: 99%
“…Experimental investigations on these compounds by doping impurities in a controlled fashion have shown that a quantitatively reasonable description of the temperature dependence of spinon mean free paths is possible by taking into account the scattering of magnetic excitations off phonons and impurities alone [1,2,5,6,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3e) might be attributed to an inevitable slight misalignment of ∇T direction from the b-axis (≤ 6 • ). We also note that the thermal conductivity of Sr 2 CuO 3 is almost isotropic [22] and, therefore, the voltage suppression cannot be attributed to a reduction in the magnitude of ∇T . The negative and anisotropic LSSE is evidence that spin current is generated and conveyed by spinons through the spin chains of the Sr 2 CuO 3 .…”
mentioning
confidence: 80%